ANALISIS EVAKUASI BENCANA TSUNAMI DI GEDUNG KULIAH BERSAMA V UNIVERSITAS BENGKULU DENGAN METODE AGENT BASED MODELLING - Sahroli, Ade; Hardiansyah, Hardiansyah (Inersia: Jurnal Teknik Sipil, 2019)
This study modeled the movement of tsunami refugees at Gedung Kuliah Bersama V University of Bengkulu with an agent based modeling method. The questionnaire was conducted to find out the modes of transportation used, then processed by finding the saturation of degree, volume, road capacity, speed and travel time. This study compares the daily movement and time of evacuation, then a simple linear regression analysis is carried out. There are several road segments and alternative routes that were reviewed in this study. The results showed that the route chosen by respondents during evacuation was the shortest route to the exit gate. The saturation of degree obtained was still in the stable category. However, there is a necessary to develop the performance of university of bengkulu road networks which can enjure the better evacuation process.